Farmers’ Participation in Climate Smart Agriculture Initiatives and Adoption Decisions in the Arsi and East Shewa Zones of Oromia Region, Ethiopia (Research in Agriculture Livestock and Fisheries, 2024)
Climate change is a major challenge to sustainable agricultural production in the world. The intricacy of the problem requires farmers’ compliance with regenerative agricultural practices that can facilitate the conservation of fragile productive systems while sustaining their productivity. Accordingly, various climate change management strategies have been promoted in Ethiopia. This paper analyzed farmers’ participation in CSA practices and the determinants of adoption in the Oromia region of Ethiopia. The data were collected during the 2020 cropping season from 420 randomly selected farmers in the Arsi (highland) and East Shewa (lowland) zones of the Oromia region. The data was analyzed with descriptive and Logit regression. The results showed that of the total thirteen climate-smart agricultural practices that were assessed, about 6 and 4 were adopted by more than 50% of the farmers in the highland and lowland, respectively. Also, 21.0% and 42.4% of respondents from highland and lowland respectively participated in CSA programs or projects. Moreover, 35.5% and 34.8% of the highland and lowland agroecology farmers respectively adopted some CSA after project participation. In highland agroecology, crop rotation, crop residual management, crop diversification, and intercropping were the mostly used practices, while crop rotation, adjustment of planting time, minimum tillage, and planning of drought-resistant varieties were mostly used by lowland agroecology farmers. Moreover, logistic regression results reveal that CSA adoption is influenced by age, education, gender, family size, credit support, experience, extension support, non-agricultural income, and livestock holding. It was concluded that adoption of CSA was low, and promotion of extension support and CSA participation experiences will facilitate adoption of some CSA practices. More importantly, extension support should focus on CSA practices that were widely used by the farmers.Res. Agric. Livest. Fish. Vol. 11, No. 1, April 2024: 79-91